Disentangling genetic and prenatal sources of familial resemblance across ontogeny in a wild passerine - Hadfield, J; Heap, E; Bayer, F; Mittell, E; Crouch, N (2013)
Cross-fostering experiments are widely used by quantitative geneticists to study genetics and by behavioral ecologists to study the effects of prenatal investment. Generally, the effects of genes and prenatal investment are confounded and the interpretation given to such experiments is largely dependent on the interests of the researcher. Using a large-scale well-controlled experiment on a wild population of blue tits (Cyanistes caeruleus), we are able to partition variation in body mass across ontogeny into the effects of genes and the effects of between-clutch variation in egg characteristics. We show that although egg effects are important early in ontogeny they quickly dissipate, suggesting that the genetic interpretation of cross-fostering experiments may be preferable for many types of trait. However, the heritability of body mass is smaller than has previously been reported. Our results suggest that this is due to a combination of controlling postnatal environmental effects more carefully and accounting for viability selection operating early in ontogeny. © 2013 The Author(s).